Interações discursivas e o uso de imagens em uma sequência multimodal de ensino sobre a água nos anos iniciais do ensino fundamental - Andreza Fortini da Silva (2012)
The aim of this work is to show how a teacher of the basic education initial years has established bonds between the students initial contributions on the subject of water and the elements that had composed the multimodal sequence of science classes. In orderto evince these bonds we examine the discursive interactions in the four first lessons of the sequence trying to find the links between events that had been evoked and developed by the teacher with intense participation of the children. We use theoretical references from qualitative analysis to formulate a critical and methodological approach of the sociohistorical perspective articulating our reflection with some main aspects of socialsemiotics. Our interest is to examine the didactic strategies lead by the teacher highlighting the presence of visual resources in the activities of text production seen as practices of alphabetization and literacy in the context of science classes. Thus we use the following analytical categories: discourse marks of the opening lesson and of the preliminarydiscussions concerning the activity in the students production; evidences of change in the initial repertoires of the students; evidences of relations between the situations that provide examples of the use of water in the daily life and that treat water as an object of science studies.We also search to analyze the drawings made by the children as a form of language and the contributions and limitations of an animated and interactive info-graphic as a resource of mediation in the process of knowledge construction in the sequence of the science lessons on the subject of water. In order to examine the effectiveness of thechildrens production of drawings as a way of meaning construction, the analyses search to understand which relations can be established between the drawings and the verbal and written texts verbal produced by the children. These analyses are made at two moments ofthe education sequence on the subject of water: in the first lesson observing the childrens preliminary ideas - and in the fourth lesson after the use of an animated infographic about the cycle of the water in the nature. The data collection was made in a third year group of Basic Formation of a public school of Contagem, metropolitan region of thecity of Belo Horizonte/Minas Gerais.